Case Study On CIMB Bank Berhad - C. Annamalai, Kanagavalli (2008)
This case study is conducted to study the overall performance of CIMB Bank. This study of home grown bank highlights its background, the history, vision, mergers, the organization structure, performance and achievement throughout the existence which were divided accordingly to its chapters in first part of the study.